PENGARUH PERTUMBUHAN ASET DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL PERUSAHAAN SEKTOR KONSUMSI PRIMER - Khoirunnisa Azzahra (Jurnal Ilmiah Raflesia Akuntansi, 2022)
Capital structure is an important factor to be analyzed by investors as a material consideration in making investment decisions in order to obtain the expected return. This study aims to analyze and obtain empirical evidence of the effect of asset growth and sales growth on the capital structure of primary consumer companies listed on the Indonesia Stock Exchange in 2016-2020. This research is a quantitative study using a descriptive method, the data used is secondary data in the form of financial statements that contain numbers are then tested and describe or provide an overview of these results. The sample selection in this study used a purposive sampling technique. The data analysis method used is panel data regression processed using Eviews version 9. The population used in this study are primary consumer companies listed on the Indonesia Stock Exchange in 2016 – 2020. The samples obtained were 51 companies with 5 years of research, the total research data obtained is 255. The results of this study indicate that asset growth has no effect on capital structure and sales growth has an influence on capital structure. Simultaneously the variables of asset growth and sales growth have an influence on capital structure.